171k views
2 votes
Evaluate each expression ​

Evaluate each expression ​-example-1
User Yating
by
5.2k points

1 Answer

2 votes

Answer:

below

Explanation:

  • c = 8 and d = -3


c^(2) + d^(3) \\8^(2) + (-3)^(3) \\64 + (-27) \\64 - 27 \\37

  • r = -3 and s = -4


( r - s)^(3) + r^(2)\\(-3 -(-4))^(2) + (-3)^(2) \\(-3+4)^(3) + 9+ \\1^(3) + 9\\1 + 9 \\10

User NOlivNeto
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.